Analisis Materi Buku Teks Bahasa Arab "Memahami Al-Qur'an Dengan Metode Manhaji Jilid I" Karya Muhammad Annas 'Adnan - Kholid Ramadhanzi, Muhammad; , Drs. Abdullah Mahmud, M, Ag (2017)
Arabic is the language of the Qur'an. The Qur'an has been keeping the Arabic language for centuries. The teaching of Arabic in Indonesia has many ways or methods used, including the use of textbooks that makes a good medium of learning, either using Arabic or Indonesian. Textbooks are one of the main elements in the curriculum beside other elements, such as process, media, and learning methods. Textbook is the foundation in all levels of education. Of the many textbooks in Arabic, researchers find an interesting book in learning Arabic such as "Understanding the Qur'an with Manhaji Method Volume I" by Muhammad Annas' Adnan, whose uniqueness appears in the preface that the Indonesian language is also a direct medium to study the Qur'an. This is the first Arabic language textbooks in Indonesia which are learning the material directly to the Qur'an. Thus, this study has been conducted to understand the feasibility of the book, as teaching materials Arabic lessons for beginners level, in terms of some theoretical preparation of textbooks as well as in terms of selection, gradation, presentations, and repetition. The purpose of this study is to determine the feasibility of a book entitled "Understanding the Qur'an with Manhaji Method Volume I" as a teaching material of Arabic lessons for beginners level, in terms of some theoretical preparation of textbooks as well as in terms of selection, gradation, presentations, and repetition. This study is a library research, then the data collection techniques are using documentation and interviews. The study has also used the method of observation looking at both primary and secondary book, while to analyze data, this research has applied content analysis. These results indicate that these textbooks do not meet the criteria of good textbooks in terms of material, which is not in accordance with the scholarly foundation, including: the accuracy of the material, the range of material, and material support while according to theory Ali Muhammad Al-Qāsimῑ, the book only meets the criteria of basic materials and certain materials, while the supporting material are not suitable. Based on the terms of selection, gradation, presentation and repetition, the book does not yet meet the criteria of a good book.